UPAYA MENINGKATKAN PRODUKSI TANAMAN TOMAT DENGAN APLIKASI GANDASIL B - Astutik Astutik; Astri Sumiati (Universitas Tribhuwana Tunggadewi, 2018)
One of efforts to increase tomato plant productions can be done by fertilization. Gandasil B was one of leaf fertilizer which can be used to fill P of plant so that it can increase the plant production. However, so far it has not been used for tomato plants. Therefore, it needs to do a research in order to find out the concentration and fertilization period of Gandasil B to tomato production. The research was conducted in Lowokwaru Village, Malang on March to August 2012. The research consisted of 8 treatment combinations, they are K0P1 (without treatment), K1P2 (1g/l per 1 week), K2P1 (2g/l per 1 week), K3P1 (3g/l per 1 week), K0P2 (without treatment), K1P2 (1g/l per 2 weeks), K2P2 (2 g/l per 2 weeks), K3P2 (3 g/l per 2 weeks). Each treatment was repeated four times.The research results can be concluded that there is concenration interaction and fertilization period to plant height at the age of 14 and 49 days after planting, leaves amount at the age of 14, 21, 28, 35, and 42 after planting, flowers amount at the age of 49 days after planting, branches amount at the age of 49 days after planting, and fruits amount. However, partially fertilization period treatment affects at flowering time, flowers amount at the age of 28.35 and 42 days after planting, and fruits weight. The best plant of Gandasil B fertilization results 25.98 fruits/plant with total weight of 1.23 kg/plant